South through the Pole 1997-98 - Arnesen, Liv (Polarboken, 2000)
Keywords: Antarktis; ekspedisjoner

Man in extreme environments - Brubakk, Alf O. (Aviation, space, and environmental medicine, 2000)
Humans have demonstrated the ability to live and work in many adverse environments. Many examples demonstrate that our understanding of humans ability to adapt to extreme environments is limited, but it is reasonable to assume that the main problems in space exploration will be psychological and social. It is argued that polar expeditions of an earlier age are a better model for space exploration than confinement studies or Antarctic overwintering. Some aspects of the reason for the success of these expeditions are discussed and the lessons that can be used are pointed out.
Supplement: S
Keywords: Antarktis; fysiologi; overvintring; polarekspedisjoner; polarområdene

Et liv i isen : polarkokken Adolf H. Lindstrøm - Ekeberg, Jan Ove (Kagge forl., 2000)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; polarekspedisjoner

Fra Haugesund til isødet i Antarktis: en hvalfanger forteller - Evensen, Karin H (Akademisk fagforlag, 2000)
Keywords: Antarktis; historie; hvalfangst

Lipids, trophic relationships, and biodiversity in Arctic and Antarctic krill - Falk-Petersen, Stig; Hagen, Wilhelm; Kattner, Gerhard; Clarke, Andrew; Sargent, John (Canadian Journal of Fisheries and Aquatic Sciences, 2000)
Environmental seasonality is a critical factor in structuring polar marine ecosystems. The extensive data now available on the lipids of Arctic and Antarctic euphausiids show that all species are characterised by a seasonally high lipid content, and neutral lipids, whether wax esters or triacylglycerols, are primarily accumulated for reproduction. The Arctic Thysanoessa inermis and the Antarctic Euphausia crystallorophias contain high levels of wax esters and higher concentrations of 18:4(n-3) and 20:5(n-3) and a lower ratio of 18:1(n-9)/(n-7) fatty acids in their neutral lipids than the Arctic Thysanoessa raschii and the Antarctic Thysanoessa macrura and Euphausia superba. Large amounts of phytol in the lipids of T. raschii and E. crystallorophias during winter suggest the ingestion of decaying algae originating in sedimenting material or in sea ice. Thysanoessa raschii, T. macrura, and E. superba have a high ratio of 18:1(n-9)/ (n-7) fatty acids, indicating animal carnivory. We conclude that T. inermis and E. crystallorophias are true high polar herbivores, while T. raschii, T. macrura, and E. superba are omnivores with a more boreal distribution. The Arctic species Thysanoessa longicaudata and Meganyctiphanes norvegica are carnivores feeding on Calanus, as indicated by high amounts of 20:1(n-9) and 22:1(n-11) fatty acids.
Keywords: Antarktis; biodiversitet; copepoder; krill; marin biologi; marine økosystemer; plankton

Spatial gradients in snow layering and 10 m temperatures at two EPICA-Dronning Maud Land (Antarctica) pre-site-survey drill sites - Holmlund, P.; Gjerde, K.; Gundestrup, N.; Hansson, M.; Isaksson, E.; Karlöf, L.; Nman, M.; Pettersson, R.; Pinglot, F.; Reijmer, C. H.; Stenberg, M.; Thomassen, M.; et al. (Annals of Glaciology, 2000)
During the 1997/98 field season, Sweden, Norway and The Netherlands performed a pre-site survey for EPICA in Dronning Maud Land, Antarctica. This paper summarizes the results and pays special attention to the high spatial gradients found in snow layering and temperatures. The sites were "Camp Victoria" (CV) on Amundsenisen (76° S, 8° W; 2400 m a.s.l.), approximately 550 km from the coast, and "Camp Maudheimvidda" (CM) on Maudheimvidda (74° S 13° W; 362 m a.s.L), some 140 km from the coast.The drilling programme included both medium-long firn/ice cores and shallow firn cores. These were analysed by means of δ18O, DEP, ECM,β activity, density, and ion content. The combined results suggests a mean annual accumulation rate of 60 mm. we. for CV and 220 mm. we. for CM.Variability measurements of spatial snow layering were performed at two scales; over tens of kilometres by radar and over a few metres by pits and high-resolution radar soundings. Results, as measured by relative standard deviation, were typically 10% on the polar plateau and as high as 50% near the coast.The 10 m temperature measurements were –38.5°C (std dev. = 0.5°) for CV and –17.6°C (std dev.=0.15°) for CM.Snow chemistry was sampled at each medium-long-core drill site. Comparison of δ18O profiles from snow pits and the uppermost part of the CV medium-long core showed large variations. Mean δ18O valuesover 2 m profiles varied between 41.6%, and 39.7%o within a horizontal distance of 50 m.
Edition: 2017/09/14 Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi; iskjerner; klimatologi

Studies of seabirds and seals on Bouvetøya 1998/99 - Isaksen, Kjell; Huyser, Onno; Kirkman, Steve; Wanles, Ross; Wilson, Wendy (2000)
Keywords: Bouvetøya; forskning; fugler; pinnipedier; seler; zoologi

A 1500 year record of accumulation at Amundsenisen western Dronning Maud Land, Antarctica, derived from electrical and radioactive measurements on a 120 m ice core - Karlöf, Lars; Winther, Jan-Gunnar; Isaksson, Elisabeth; Kohler, Jack; Pinglot, Jean Francis; Wilhelms, Frank; Hansson, Margareta; Holmlund, Per; Nyman, M; Pettersson, Rikard; Stenberg, Malin; Thomassen, M P A; et al. (Journal of Geophysical Research: Atmospheres, 2000)
During the Nordic EPICA pre-site survey in Dronning Maud Land in 1997/1998 a 120 m long ice core was retrieved (76°00′S 08°03′W, 2400 m above sea level). The whole core has been measured using the electric conductivity measurement (ECM) and dielectric profiling (DEP) techniques, and the core chronology has been established by detecting major volcanic eruptions. In a nearby shallow core radioactive traces from nuclear tests conducted during the 1950s and 1960s have been identified. Altogether, 13 ECM and DEP peaks in the long core are identified as originating from specific volcanic eruptions. In addition two peaks of increased total β activity are identified in the short core. Accumulation is calculated as averages over the time periods between these dated events. Accumulation rate is 62 millimetres (w. eq./yr) for the last 181 years (1816 A.D. to present) and 61 mm w. eq./yr for the last 1457 years (540 A.D. to present). Our record shows an 8% decrease in accumulation between 1452 and 1641 A.D. (i.e. part of the Little Ice Age), compared to the long-term mean.
Keywords: Dronning Maud Land; geofysikk; glasiologi; innlandsis; iskjerner; paleoklimatologi

Geochronologic evidence for Early Cretaceous volcanic activity on Barton Peninsula, King George Island, Antarctica - Kim, Hyeoncheol; Ik Lee, Jong; Young Chose, Moon; Cho, Moonsup; Zheng, Xiangshen; Sang, Haiquing; Qiu, Ji (Polar Research, 2000)
Ages of six volcanic and plutonic rocks on Barton Peninsula, King George Island, were determined using 40Ar/39Ar and K-Ar isotopic systems. The 40Ar/39Ar and K-Ar ages of basaltic andesite and diorite range from 48 My to 74 My and systematically decrease toward the upper stratigraphic section. Two specimens of basaltic andesite which occur in the lowermost sequence of the peninsula, however, apparently define two distinct plateau ages of 52-53 My and 119-120 My. The latter is interpreted to represent the primary cooling age of basaltic andesite, whereas the former is interpreted as the thermally-reset age caused by the intrusion of Tertiary granitic pluton. The isochron ages calculated from the isotope correlation diagram corroborate our interpretation based on the apparent plateau ages. It is therefore likely that volcanism was active during the Early Cretaceous on Barton Peninsula. When the K-Ar ages of previous studies are taken into account with our result, the ages of basaltic andesite in the northern part of the Barton Peninsula are significantly older than those in the southern part. Across the north-west-south-east trending Barton fault bounding the two parts, there are significant differences in geochronologic and geologic aspects.
Keywords: Antarktis; geokronologi; geologi; vulkaner

Diet and estimated food consumption of Antarctic fur seals at Bouvetøya during summer - Kirkman, Stephen; Wilson, W.; Klages, Norbert; Bester, Marthán; Isaksen, Kjell (Polar Biology, 2000)
Collection and analysis of natural regurgitations and fresh scats, deposited by Antarctic fur seals at the Nyrøysa colony, Bouvetøya, during December 1998 to February 1999, afforded a comprehensive description of the dietary composition of this expanding population during the summer months. Mature, adult Euphausia superba was the staple diet of fur seals at Nyrøysa, while squid and myctophid fish appeared to be taken opportunistically. In metric tons, the total Bouvetøya fur seal population is estimated to have consumed a minimum of 14,365 t krill (representing 1.2713 × 1010 individuals of 1.13 g mass), 186 t fish, 184 t squid and 14,735 t over 3 months, but there are many possible sources of error in these estimates. It is presumed that over-indulgence in krill may cause animals to regurgitate ashore.
Keywords: Bouvetøya; marin biologi; pelsseler; pinnipedier; seler; zoologi

Effort explores 130 Million years of Antarctic paleoenvironment - Kristoffersen, Yngve; Goodwin, Ian D; Cooper, Alan K (Eos, Transactions American Geophysical Union, 2000)
Antarctic climate history has been dominated by events and turning points with causes that are poorly understood. To fill the gaps in our knowledges new effort is underway in the international geologic community to acquire and coordinate the circum-Antarctic geologic data needed to derive and model paleoenvironments of the past 130 m.y. The effort, which focuses principally on using shallow (<100 m) stratigraphic drilling and coring to acquire the geologic data, is being led by the Antarctic Offshore Stratigraphy Project (ANTOSTRAT), a group that works under the aegis of the Scientific Committee on Antarctic Research (SCAR). About 40 scientists from 12 countries met this past summer in Wellington, New Zealand, at an ANTOSTRAT meeting to discuss strategies for implementing the desired paleoenvironmental field and modeling studies. The meeting was held in conjunction with the 8th International Symposium on Antarctic Earth Sciences.
Keywords: Antarktis; geologi; geovitenskap; klimatologi; paleontologi; stratigrafi

Pilot shallow drilling on the continental shelf, Dronning Maud Land, Antarctica - Kristoffersen, Yngve; Strand, Kari; Vorren, Tore; Harwood, Dave; Webb, Peter (Antarctic Science, 2000)
A light, mining drill rig deployed from the stern of a research vessel has been used to carry out shallow drilling in 212 m water depth on the continental shelf in the eastern Weddell Sea. Penetration was 15 m below the seabed with 18% recovery in the 31 hours available for the experiment. The recovered glacigenic sediments are predominantly volcanic material of basaltic and andesitic composition with petrological characteristics and age similar to the continental flood basalts exposed in Vestfjella, about 130 km upstream from the drill site. The sediments include a reworked marine Miocene diatom flora. The material documents oscillations of the East Antarctic Ice Sheet over the past 30 ka. The lowermost diamicton probably represents a deformation till, and the grounding line retreated past the drill site 30 km from the shelf edge about 30 kyr BP. A readvance occurred during the Late Wisconsin Glacial Maximum. Assuming a reservoir correction of 1300 yr, marine conditions existed at the site between 10.1-7 kyr BP, and later at least between 2.8 and 2.5 kyr BP. The stratigraphy at the site has been disturbed by iceberg ploughing and/or contact between the ice shelf and the sea floor during local advances after 2.5 kyr BP.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; Weddellhavet; geokjemi; geologi; glasiologi; havbunnen; innlandsis; isshelf; kontinentalsokkel; stratigrafi

Shelf progradation on a glaciated continental margin, Queen Maud Land, Antarctica - Kristoffersen, Yngve; Winterhalter, Boris; Solheim, Anders (Marine Geology, 2000)
A detailed survey of the continental margin in the eastern Weddell Sea demonstrates shelf progradation by material input from discrete glacial wedges that amalgamate to form the present near rectilinear shelf edge. Kvitkuven Ice Rise is located between two trough mouth fans and rests on a thick sediment substratum that predates the shelf sequences north of it. Shelf progradation, west of the ice rise, preceded the progradation east of it. In this way the seaward progression of a shelf edge may reflect the broad scale expansion of the East Antarctic Ice Sheet, but the timing of shelf progradation can be different in adjacent areas. The progradational glacial wedges on the continental shelf mapped by this survey are correlated stratigraphically to be within the post Late Miocene glacial sequence, drilled at ODP Site 693 on the middle continental slope 200 km to the northeast. Two submarine moraine ridge complexes on the shelf parallel the shelf edge. A radiocarbon age of 18:950 280 years BP from the front of the inner complex (water depth 319 m) suggests that grounded ice at most reached the present mid-shelf area in front of the ice rise during the Late Wisconsin Glacial Maximum, or had retreated to this position at that time.
Keywords: Dronning Maud Land; Weddellhavet; marin geofysikk; marin geologi; oseanografi; seismisk stratigrafi

Combined characterisation of GOME and TOMS total ozone measurements from space using ground-based observations from the NDSC - Lambert, J.-C.; Van Roozendael, M.; Simon, P.C.; Pommereau, J.-P.; Goutail, F.; Gleason, J.F.; Andersen, S.B.; Arlander, D.W.; Bui Van, N.A.; Claude, H.; de La Noë, J.; De Mazière, M.; et al. (Advances in Space Research, 2000)
Several years of total ozone measured from space by the ERS-2 GOME, the Earth Probe TOMS, and the ADEOS TOMS, are compared with high-quality ground-based observations associated with the Network for the Detection of Stratospheric Change (NDSC), over an extended latitude range and a variety of geophysical conditions. The comparisons with each spaceborne sensor are combined altogether for investigating their respective solar zenith angle (SZA) dependence, dispersion, and difference of sensitivity. The space- and ground-based data are found to agree within a few percent on average. However, the analysis highlights for both GOME and TOMS several sources of discrepancies: (i) a SZA dependence with TOMS beyond 80° SZA; (ii) a seasonal SZA dependence with GOME beyond 70° SZA; (iii) a difference of sensitivity with GOME at high latitudes; (iv) a difference of sensitivity to low ozone values between satellite and SAOZ sensors around the southern tropics; (v) a north/south difference of TOMS with the ground-based observations; and (vi) internal inconsistencies in GOME total ozone.
Keywords: Antarktis; fjernmåling; geofysikk; meteorologi; ozonlaget; polarområdene; satellitt observasjoner

Snow and blue-ice distribution patterns on the coastal Antarctic Ice Sheet - Liston, Glen E.; Winther, Jan-Gunnar; Bruland, Oddbjørn; Elvehøy, Hallgeir; Sand, Knut; Karlöf, Lars (Antarctic Science, 2000)
Surface patterns of alternating snow and blue-ice bands are found in the Jutulgryta area of Dronning Maud Land, Antarctica. The snow-accumulation regions exist in the lee of blue-ice topographic ridges aligned perpendicular to winter winds. The snow bands are c. 500–2000 m wide and up to several kilometres long. In Jutulgryta, these features cover c. 5000 km2. These alternating snow and blue-ice bands are simulated using a snow transport and redistribution model, SnowTran-3D, that is driven with a winter cycle of observed daily screen-height air temperature, humidity, and wind speed and direction. The snow-transport model is coupled to a wind model that simulates wind flow over the relatively complex topography. Model results indicate that winter winds interact with the ice topographic features to produce alternating surface patterns of snow accumulation and erosion. In addition, model sensitivity simulations suggest that subtle topographic variations, on the order of 5m elevation change over a horizontal distance of 1 to 1.5 km, can lead to snow-accumulation variations that differ by a factor of six. This result is expected to have important consequences regarding the choice of sites for ice-coring efforts in Antarctica and elsewhere.
Edition: 2004/05/06 Publisher: Cambridge University Press
Keywords: Dronning Maud Land; blåis; geofysikk; glasiologi; iskjerner

Molecular Evidence for Extrapair Paternity and Female-Female Pairs in Antarctic Petrels - Lorentsen, Svein-Håkon; Amundsen, Trond; Anthonisen, Kristin; Lifjeld, Jan T. (The Auk, 2000)
Considerable interspecific variation exists in the frequency of extrapair fertilizations (EPFs) in birds. In general, EPFs are more common and occur at higher frequencies in passerines than in nonpasserines (Westneat and Sherman 1997). Lower rates of EPFs are typical for territorial nonpasserines as well as those that breed colonially (Westneat and Sherman 1997). This seems to contradict Birkhead and Møller's (Birkhead and Møller 1992, Møller and Birkhead 1993) hypothesis of intense sperm competition in colonial birds. Their arguments were based on the assumption that the need for nest defense in dense aggregations restricts the ability of males to guard their mates, and that the high number of potential extrapair mates available in colonies selects for a high rate of extrapair copulations (EPCs). In contrast, Westneat and Sherman (1997) found no correlation across species between the frequency of EPFs and nesting dispersion, local breeding density, or breeding synchrony, although EPFs were related to nesting density within species. This suggests that EPC rates are not informative regarding EPF rates in colonial birds (Westneat and Sherman 1997), or that the pattern reported by Møller and Birkhead (1993) does not hold true when more species are included. The conflicting evidence regarding the relationship between extrapair activities and breeding density calls for more empirical studies, especially among colonial nonpasserines. Social monogamy is the predominant mating system in the Procellariiformes (Warham 1990). Several aspects of their breeding biology may, however, provide favorable opportunities for extrapair sexual activity. First, colonial breeding provides ample opportunities for EPCs because many potential partners are available at close range (Birkhead and Møller 1992, Møller and Birkhead 1993). Second, when the sexes are spatially and/or temporally separated, as may be the case in procellariiforms where adults seek food far from the colony, males have few cues to assess whether their mates have been unfaithful. Hence, few reasons exist to expect a facultative decrease in male parental investment if cuckolded, in contrast to the case for many territorial species where a male may have more reliable cues to his mate's unfaithfulness (e.g. female disappearance, high intrusion rate, etc.). Accordingly, colonial breeding may facilitate EPCs for both sexes, and colonial species may be expected to display high rates of EPC. Paternity studies require error-free sex determination of adults. This is straightforward for clearly dimorphic species, or if sex determination can be done from genitalia during the fertile period. But if fieldwork can be performed only during the nestling period, sex determination may be problematic for largely monomorphic species, and indirect methods must be used. In the Antarctic Petrel (Thalassoica antarctica), the two sexes differ slightly in mean body size. Lorentsen and Røv (1994) used this difference to determine the sex of Antarctic Petrels by discriminant function analysis (DFA). The procedure correctly determined the sex of 92% of the birds in a sample from the same year. This does not necessarily imply a similar resolution if the discriminant function is adopted for samples from other years, or if data are collected by other observers. Moreover, although useful for many purposes, 92% resolution in sex determination is insufficient for paternity studies. Therefore, we performed molecular sexing of all breeding adults according to the PCR-based method of Griffiths et al. (1998). The main aim of our study was to analyze whether extrapair paternity occurs in a colonial procellariiform, the Antarctic Petrel. We also tested the robustness of morphological sex determination (from DFA) across seasons relative to that obtained from molecular techniques.
Keywords: Dronning Maud Land; NARE 1993/94; fugler; ornitologi; petreller; zoologi

IFIX - inductive data acquisition system: system for sub ice shelf data acquisition - Lothe, Torleif (Filchner-Ronne Ice Shelf Programme. Report, 2000)
Keywords: Antarktis; Sørishavet; forskning; teknologi

Flood Basalts of Vestfjella: Jurassic Magmatism Across an Archaean–Proterozoic Lithospheric Boundary in Dronning Maud Land, Antarctica - Luttinen, Arto V.; Furnes, Harald (Journal of Petrology, 2000)
Continental flood basalts (CFBs) of Jurassic age make up the Vestfjella mountains of western Dronning Maud Land and demonstrate an Antarctic extension of the Karoo large igneous province. A detailed geochemical study of the 120-km-long Vestfjella range shows the CFB suite to consist mainly of three intercalated basaltic rock types designated CT1, CT2 and CT3 (chemical types 1, 2 and 3) that exhibit different incompatible trace element ratios. CT1 and CT2 of north Vestfjella record wide ranges of Nd and Sr isotopic compositions with initial εNd and εSr ranging from +7·6 to −16·0 and −16 to +65, respectively. The southern Vestfjella is dominated by CT3 with near-chondritic εNd (+2·0 to −4·1) and εSr (−11 to +19). A volumetrically minor suite of ocean island basalt (OIB-)like CT4 dykes (εNd +3·6, εSr +1) cuts the lava sequence in north Vestfjella. The pronounced isotopic differences suggest different magmatic plumbing systems for the heterogeneous CT1 and CT2 suites and the relatively homogeneous CT3 lavas. This is further supported by the palaeoflow directions, which point to major source regions to the north (CT1 and CT2) and east (CT3) of Vestfjella. These source regions can be associated with two contemporaneous major lithospheric thinning zones that permitted magma emplacement and controlled the melting of upper-mantle sources in the Jurassic Dronning Maud Land. The CT1 and CT2 magmas utilized the northern zone of thinning and were emplaced into the 3 Ga Grunehogna craton, whereas the CT3 magmas were emplaced through thinned Proterozoic Maud Belt lithosphere. Trace element and isotopic studies of the identified magma types reveal a complex history of fractionation and contamination at different lithospheric levels. All extrusive rock types show evidence of crustal contamination but this had rather small impact on their diagnostic trace element ratios. Much stronger overprint, in the CT1 and CT2 suites, resulted from contamination with veined Archaean lithospheric mantle, which produced wide ranges of isotopic and highly incompatible element ratios. CT3, in turn, does not show evidence of interaction with the Proterozoic lithospheric mantle. The high-εNd endmembers of CT1, CT2 and CT3 probably closely resemble uncontaminated mantle-derived magmas and indicate three different mantle sources. The CT2 primary magmas were derived from light rare earth element (LREE)-depleted, slightly large ion lithophile element (LILE)-enriched sources, whereas data on the volumetrically preponderant CT1 and CT3 point to variably LREE-enriched, strongly LILE-enriched sources. The sources of CT1, CT2 and CT3 may record large-scale lateral heterogeneity generated by subduction-contamination of the Gondwanan upper mantle. The OIB-like CT4 dykes probably reflect asthenospheric heterogeneities that were unrelated to the proposed subduction-contamination.
Keywords: Dronning Maud Land; geokjemi; geologi; petrografi; petrologi

Subglacial topography of Jutulstraumen outlet glacier, East Antarctica, mapped from ground-penetrating radar, optical and interferometric synthetic aperture radar satellite data - Melvold, Kjetil; Rolstad, Cecilie Eie (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 2000)
Publisher: Routledge
Keywords: Antarktis; geologi; glasiologi; isstrøm; topografi

Oceanographic observations south of Berkner Island: preliminary results - Nicholls, Keith W; Østerhus, Svein; Makinson, Keith; Johnson, Mark (Filchner-Ronne Ice Shelf Programme. Report, 2000)
Keywords: Sørishavet; oseanografi

Etableringen av Norsk polarinstitutt i 1948 : gammel vin i nye skinnsekker? - Nilsen, Frode (Universitetet i Tromsø, 2000)
Publication Title: Institutt for historie. Det samfunnsvitenskapelige fakultet
Keywords: Antarktis; Norsk Polarinstitutt; historie; internasjonal; polarområdene; politikk

Norway: Implementing the Protocol on Environmental Protection - Njåstad, Birgit (Implementing the Environmental Protection Regime for the Antarctic, 2000)
Keywords: Antarktis; Antarktistraktaten; miljøprotokollen; miljøvern

The Committee for Environmental Protection: Its Establishment, Operation and Role within the Antarctic Treaty System - Orheim, Olav (Implementing the Environmental Protection Regime for the Antarctic, 2000)
Keywords: Antarktis; miljø; miljøkonsekvensanalyser; miljøpåvirkning

Hvite horisonter - Oterhals, Leo (Lagunen, 2000)
Keywords: Antarktis; Sørishavet; ekspedisjoner; historie

Arctic and Antarctic ozone layer observations: chemical and dynamical aspects of variability and long-term changes in the polar stratosphere - Rex, Markus; Dethloff, Klaus; Handorf, Dörthe; Herber, Andreas; Lehmann, Ralph; Neuber, Roland; Notholt, Justus; Rinke, Annette; von der Gathen, Peter; Weisheimer, Antje; Gernandt, Hartwig (Polar Research, 2000)
The altitude dependent variability of ozone in the polar stratosphere is regularly observed by balloon-borne ozonesonde observations at Neumayer Station (70°S) in the Antarctic and at Koldewey Station (79°N) in the Arctic. The reasons for observed seasonal and interannual variability and long-term changes are discussed. Differences between the hemispheres are identified and discussed in light of differing dynamical and chemical conditions. Since the mid- 1980s, rapid chemical ozone loss has been recorded in the lower Antarctic stratosphere during the spring season. Using coordinated ozone soundings in some Arctic winters, similar chemical ozone loss rates have been detected related to periods of low temperatures. The currently observed cooling trend of the stratosphere, potentially caused by the increase of anthropogenic greenhouse gases, may further strengthen chemical ozone removal in the Arctic. However, the role of internal climate oscillations in observed temperature trends is still uncertain. First results of a 10000 year integration of a low order climate model indicate significant internal climate variability. on decadal time scales, that may alter the effect of increasing levels of greenhouse gases in the polar stratosphere.
Keywords: Antarktis; drivhusgasser; klimaendringer; klimagasser; meteorologi; observasjoner; ozonlaget; polarområdene; stratosfæren

The large-scale dynamics of Jutulstraumen drainage basin, East Antarctica - Rolstad, Cecilie Eie (Unipub forlag, 2000)
Publication Title: Faculty of Mathematics and Natural Sciences, University of Oslo
Keywords: Antarktis; Sydpolen; geografi; glasiologi

Large-scale force budget of an outlet glacier: Jutulstraumen, Dronning Maud Land, East Antarctica - Rolstad, Cecilie; Whillans, Ian M.; Hagen, Jon Ove; Isaksson, Elisabeth (Annals of Glaciology, 2000)
A large-scale force budget was applied using a combination of remote-sensing and field data from Jutulstraumen, Dronning Maud Land, Antarctica. In the grounded area, more than 95 % of ice flow is balanced by basal friction. In a partly floating section near the grounding-line area, on average lateral drag provides 38% of resistance to flow. Measurement uncertainties were propagated through the calculation of forces. The accuracies of strain rates derived from satellite data (Landsat thematic mapper) were found adequate to calculate meaningful force-balance terms. For the floating section, where lateral forces contribute to controlling flow, the main contribution to errors in the force budget is uncertainty in the rate factor for the flow law of ice. For grounded sections, the uncertainty in ice thickness, as measured by ground-penetrating radar, contributes more or less equally to errors in the force budget as does that in the rate factor.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; fjernanalyse; glasiologi; isstrøm; satellittbilder

Henryk Johan Bull (1893-1895). Carsten E. Borchgrevink (1898-1900). Roald Amundsen (1910-1912) - Rosove, Michael H (Let heroes speak : Antarctic explorers, 1772-1922, 2000)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Henrik Johan Bull; Roald Amundsen; Sydpolen; biografier; oppdagelsesreiser; polarekspedisjoner

Coping in Antarctica: is it possible to generalize results across settings? - Sandal, Gro Mjeldheim (Aviation Space and Environmental Medicine, 2000)
Background: To gain knowledge about psychological issues in space, data have been collected from groups in isolated and confined settings on Earth. This study examines the possibility of generalizing psychological findings across such environments. HYPOTHESIS: Psychological reactions among personnel in different Antarctic environments show similar time patterns. Antarctic personnel differ in personality from submariners to crews confined in hyperbaric chambers to military recruits. METHOD: Psychological reactions were evaluated by the Revised Antarctic Questionnaire. The Personality Characteristic Inventory was used to measure personality. RESULTS: Personnel stationed on a ship (n = 19) showed high coping during the whole mission, whereas personnel on land bases (n = 18) showed a marked decline around the third quarter. Reduced coping in the land-based groups was associated with stress from interpersonal relationships. Compared with submariners (n = 54) and hyperbaric chamber crews (n = 20), Antarctic personnel scored lower on competitiveness and higher on achievement striving. CONCLUSIONS: Similarities in physical, individual and group characteristics should be considered before extrapolating psychological findings across settings.
Keywords: Antarktis; overvintring; polarekspedisjoner; polarforskere; polarområdene; psykologi

Havforskning i tung sjø - Schwach, Vera (Havet, fisken og vitenskapen: fra fiskeriundersøkelser til havforskningsinstitutt 1860-2000, 2000)
Keywords: Sørishavet; forskning; historie; hvalfangst; pelagisk

Pingviner - Skår, Astrid (Landbruksforlaget, 2000)
Keywords: Antarktis; Sørishavet; fugler; zoologi

The impact of greenhouse gases and halogenated species on future solar UV radiation doses - Taalas, Petteri; Kaurola, Jussi; Kylling, Arve; Shindell, Drew; Sausen, Robert; Dameris, Martin; Grewe, Volker; Herman, Jay; Damski, Juhani; Steil, Benedikt (Geophysical Research Letters, 2000)
The future development of stratospheric ozone layer depends on the concentration of chlorine and bromine containing species. The stratosphere is also expected to be affected by future enhanced concentrations of greenhouse gases. These result in a cooling of the winter polar stratosphere and to more stable polar vortices which leads to enhanced chemical depletion and reduced transport of ozone into high latitudes. One of the driving forces behind the interest in stratospheric ozone is the impact of ozone on solar UV-B radiation. In this study UV scenarios have been constructed based on ozone predictions from the chemistry-climate model runs carried out by GISS, UKMO and DLR. Since cloudiness, albedo and terrain height are also important factors, climatological values of these quantities are taken into account in the UV calculations. Relative to 1979–92 conditions, for the 2010–2020 time period the GISS model results indicate a springtime enhancement of erythemal UV doses of up to 90% in the 60–90 °N region and an enhancement of 100% in the 60–90 °S region. The corresponding maximum increases in the annual Northern Hemispheric UV doses are estimated to be 14% in 2010–20, and 2% in 2040–50. In the Southern Hemisphere 40% enhancement is expected during 2010–20 and 27% during 2040–50.
Keywords: Antarktis; UV-stråling; drivhusgasser; klimaendringer; klimatologi; ozonlaget; polarområdene; ultrafiolett stråling

Very little in situ produced radiocarbon retained in accumulating Antarctic ice - van der Kemp, Wybe J.M.; Alderliesten, Cees; van der Borg, Klaas; Holmlund, Per; de Jong, Arie F.M.; Karlöf, Lars; Lamers, R.A.N.; Oerlemans, Johannes; Thomassen, Martijn P.A.; van de Wal, Roderik S.W. (8th International Conference on Accelerator Mass Spectrometry, 2000)
Ice samples from Dronning Maud Land, Antarctica, were analyzed for 14CO2 and 14CO by accelerator mass spectrometry. Only a small amount (∼2%) of in situ produced radiocarbon was detected. The calibrated radiocarbon ages, corrected for in situ produced 14C, are in fair agreement with age estimates obtained from stratigraphical methods added to a gas inclusion model. The ages of the entrapped air range from recent to ca. 1200 AD.
Keywords: Dronning Maud Land; fysikk; karbondatering; karbondioksid; kjemi; massespektrometri

Determination of Q1, an unknown organochlorine contaminant, in human milk, Antarctic air, and further environmental samples - Vetter, Walter; Alder, Lutz; Kallenborn, Roland; Schlabach, Martin (Environmental Pollution, 2000)
Q1, an organochlorine component with the molecular formula C(9)H(3)Cl(7)N(2) and of unknown origin was recently identified in seal blubber samples from the Namibian coast (southwest of Africa) and the Antarctic. In these samples, Q1 was more abundant than PCBs and on the level of DDT residues. Furthermore, Q1 was more abundant in seals from the Antarctic than the Arctic. To prove this assumption, gas chromatography-electron-capture negative ion mass spectrometry (GC/ECNI-MS), which is sensitive and selective for Q1, allowed for screening of traces of Q1 even in samples with particularly high levels of other organochlorine contaminants. Q1 was isolated by high-performance liquid chromatography (HPLC) from a skua liver sample. A 1:1 mixture with trans-nonachlor in electron-capture detectors (ECDs) was used to determine the relative response factor with ECNI-MS. The ECNI-MS response of Q1 turned out to be 4.5 times higher than that of trans-nonachlor in an ECD. With GC/ECNI-MS in the selected ion-monitoring mode, four Antarctic and four Arctic air samples were investigated for the presence of Q1. In the Antarctic air samples, Q1 levels ranged from 0.7 to 0.9 fg/m(3). In Arctic air samples, however, Q1 was below the detection limit (<0.06 fg/m(3) or 60 ag/m(3)). We also report on high Q1 levels in selected human milk samples (12-230 microg/kg lipid) and, therefore, suggested that the unknown Q1 is an environmental compound whose origin and distribution should be investigated in detail. Our data confirm that Q1 is a bioaccumulative natural organochlorine product. Detection of a highly chlorinated natural organochlorine compound in air and human milk is novel.
Keywords: Antarktis; forurensning; kromatografi; miljøgifter; miljøovervåking; toksikologi

Implementing the environmental protection regime for the antarctic - Vidas ed., Davor (Kluwer, 2000)
Publication Title: Environment & policy Issue: 28
Keywords: Antarktis; jus; miljøvern

Emerging Law of the Sea Issues in the Antarctic Maritime Area: A Heritage for the New Century? - Vidas, Davor (Ocean Development & International Law, 2000)
This article focuses on three emerging law of the sea issues for states cooperating in management of the Antarctic and its maritime area. The first of these is no newcomer: How to regulate the dramatic increase in illegal, unregulated and unreported fishing of Patagonian toothfish (Dissostichus eleginoides) in the Southern Ocean? The second question, according to the letter of the UN Convention on the Law of the Sea, awaits the countries claiming sovereignty over portions of territory in the Antarctic 10 years from the entry into force of the Convention for each of them. The question here is what to do with the requirement contained in that Convention relating to the submission of information on the outer limit of the continental shelf beyond 200 nautical miles to the Commission on the Continental Shelf? Finally, there is a third tricky question: Who is competent to regulate, and accordingly to ban, mineral activities in the Southern Ocean seabed? Is it the International Seabed Authority as the global body, or the Antarctic Treaty Consultative Parties through their regional cooperation? This question may well never be put on the policy agenda for any global forum; but it may well be posed at any time and by any third party, whether in the UN General Assembly or, more likely, in the Assembly of the International Seabed Authority.
Publisher: Taylor & Francis
Keywords: Antarktis; Antarktistraktaten; Sørishavet; fiskeri; havrett; internasjonal rett; kontinentalsokkel

Protecting the polar marine environment : law and policy for pollution prevention - Vidas, Davor (ed.) (Cambridge University Press, 2000)
Keywords: Antarktis; forurensning; hav; miljørett; miljøvern; polarområdene; skadeforebygge

The ATS on the Web: Introducing Modem Information Technology in Antarctic Affairs - Vidas, Davor; Njåstad, Birgit (Implementing the Environmental Protection Regime for the Antarctic, 2000)
Keywords: Antarktis; Antarktistraktaten; miljøprotokollen; miljøvern

Johan Koren : feltzoolog og polar-pioner - Wikan, Steinar (Schibsted, 2000)
EN NORSK FELTZOOLOG OG POLAR-PIONER 17 år gammel drar snekkerlærlingen JOHAN KOREN ut fra hjembyen i Fredrikstad i 1897 som deltager i historiens første overvintringekspedisjon i Antarktis, Belgica-ekspedisjonen. Styrmann om bord er en landsmann, den unge Roald Amundsen. I likhet med ham, blir Koren snart kjent og omtalt som en av tidenes dristigste oppdagelsesreisende, med Antarktis og Arktis som virkefelt. Men for Koren blir berømmelsen ikke varig. Bare 39 år gammel dør han i spanskesyken, alene på et hospital i Vladivostok. Og med tiden går det slik at han blir "Gutten Norge glemte" - slik tittelen lød på en senere guttebok, inspirert av hans begivenhetsrike og dramatiske liv. Blant feltzoologer regnes han imidlertid den dag i dag som en pionerskikkelse, og rundt om i verdens zoologiske museer finnes tusenvis av vitnesbyrd om hans innsats for vitenskapen som samler av fugle- og dyrearter. Forfatteren, historikeren og biologen STEINAR WIKAN bygger denne beretningen på Johan Korens delvis bevarte dagbøker, samtlige brev, dokumenter og presseomtaler, erindringsbøker og - ikke minst - samtaler med en gammel mann i det fjerneste Sibir som kjente Koren.
Keywords: Antarktis; Belgica ekspedisjon; biografier; forskning; oppdagelser; overvintring; polarekspedisjoner; zoologi

Postsealing genetic variation and population structure of two species of fur seal (Arctocephalus gazella and A. tropicalis) - Wynen, Louise P.; Goldsworthy, Simon D.; Guinet, Christophe; Bester, Marthán N.; Boyd, Ian L.; Gjertz, Ian; Hofmeyr, Greg J. G.; White, Robert W. G.; Slade, Rob (Molecular Ecology, 2000)
Abstract Commercial sealing in the 18th and 19th centuries had a major impact on the Antarctic and subantarctic fur seal populations (Arctocephalus gazella and A. tropicalis) in the Southern Ocean. The intensive and unrestricted nature of the industry ensured substantial reductions in population sizes and resulted in both species becoming locally extinct at some sites. However, both species are continuing to recover, through the recolonization of islands across their former range and increasing population size. This study investigated the extent and pattern of genetic variation in each species to examine the hypothesis that higher levels of historic sealing in A. gazella have resulted in a greater loss of genetic variability and population structure compared with A. tropicalis. A 316-bp section of the mitochondrial control region was sequenced and revealed nucleotide diversities of 3.2% and 4.8% for A. gazella and A. tropicalis, respectively. There was no geographical distribution of lineages observed within either species, although the respective ΦST values of 0.074 and 0.19 were significantly greater than zero. These data indicate low levels of population structure in A. gazella and relatively high levels in A. tropicalis. Additional samples screened with restriction endonucleases were incorporated, and the distribution of restriction fragment length polymorphism (RFLP) and sequence haplotypes were examined to identify the main source populations of newly recolonized islands. For A. tropicalis, the data suggest that Macquarie Island and Iles Crozet were probably recolonized by females from Marion Island, and to a lesser extent Ile Amsterdam. Although there was less population structure within A. gazella, there were two geographical regions identified: a western region containing the populations of South Georgia and Bouvet?ya, which were the probable sources for populations at Marion, the South Shetland and Heard Islands; and an eastern region containing the panmictic populations of Iles Kerguelen and Macquarie Island. The latter region may be a result of a pronounced founder effect, or represent a remnant population that survived sealing at Iles Kerguelen.
Publisher: John Wiley & Sons, Ltd
Keywords: Bouvetøya; Sørishavet; genetikk; marin biologi; pinnipedier; seler